Analisis Semiotika Pesan Moral Dalam Film 200 Pounds Beauty Versi Indonesia - Ramadhani Dwi Safitri; Yanto Yanto; Sapta Sari (Universitas Dehasen Bengkulu, 2024)
Film is one of the works of art from mass media that is in great demand by many people, making movies have their own place for many people. Movies also function as a place to convey moral messages, usually in the form of good values that can be used as examples or examples for the audience. In this study, moral messages are depicted in the Indonesian version of the 200 Pounds Beauty movie directed by Ody Harahap in 2023. This research aims to find out what moral messages are contained in the Indonesian version of the 200 Pounds Beauty movie. The research method used is descriptive qualitative research using data collection techniques of observation, documentation, and supporting data from books, articles, and journals. Where data analysis uses Charles Sanders Pierce’s semiotics using the triangle theory of meaning, namely the representamen, object and interpretation. The results of this study indicate that there are seven moral message contents in it, namely First, patience and sincerity are shown by accepting all insults and trials of life gracefully. Second, children's affection for parents is shown in the scene of not leaving parents regardless of their condition. Third, the caring attitude shown in the scene is willing to do anything for someone. Fourth, the meaning of friendship is shown by feeling each other and reminding each other in terms of goodness. Fifth Thinking before acting is that all actions must be taken with consideration not to make people harmed. Sixth love yourself by not listening to others who make us hurt and feel insecure. Seventh honesty shown by revealing to everyone who the real identity is without being covered up again. Film is one of the works of art from mass media that is in great demand by many people, making movies have their own place for many people. Movies also function as a place to convey moral messages, usually in the form of good values that can be used as examples or examples for the audience. In this study, moral messages are depicted in the Indonesian version of the 200 Pounds Beauty movie directed by Ody Harahap in 2023. This research aims to find out what moral messages are contained in the Indonesian version of the 200 Pounds Beauty movie. The research method used is descriptive qualitative research using data collection techniques of observation, documentation, and supporting data from books, articles, and journals. Where data analysis uses Charles Sanders Pierce’s semiotics using the triangle theory of meaning, namely the representamen, object and interpretation. The results of this study indicate that there are seven moral message contents in it, namely First, patience and sincerity are shown by accepting all insults and trials of life gracefully. Second, children's affection for parents is shown in the scene of not leaving parents regardless of their condition. Third, the caring attitude shown in the scene is willing to do anything for someone. Fourth, the meaning of friendship is shown by feeling each other and reminding each other in terms of goodness. Fifth Thinking before acting is that all actions must be taken with consideration not to make people harmed. Sixth love yourself by not listening to others who make us hurt and feel insecure. Seventh honesty shown by revealing to everyone who the real identity is without being covered up again.